Research on the influencing factors of entrepreneurial intentions based on mediating effect of self-actualization. Issue 3 (11th October 2019) - Dong, Yinhong; Pang, Lilan; Fu, Lili
Abstract : Purpose: Using statistical analysis, this paper aims to understand and investigate the factors for starting a new company successfully. Indicators from the literature and the data analysis prove that entrepreneurial environment, ability, intentions and self-actualization affect the success rate of entrepreneurship. Design/methodology/approach: To analyze the success factors for entrepreneurship, the authors take entrepreneurial environment and entrepreneurial ability as the independent variables, self-actualization as the mediating variable and entrepreneurial intentions as the dependent variable. Then, the authors build the frame model of the influencing factors according to entrepreneurial intentions based on the self-actualization mediating effect of college students. At last, four hypotheses are proposed based on this frame model. Findings: The empirical research proves that the better the entrepreneurial environment, the stronger the entrepreneurial intentions of college students; the stronger the entrepreneurial ability of students, the stronger the entrepreneurial intentions; and under the mediating effect of self-actualization, entrepreneurial environment and entrepreneurial ability will affect entrepreneurial intentions strongly. Finally, based on the empirical results, this paper proposes to pay attention to entrepreneurship education and strengthen the construction of the entrepreneurial environment to better enhance entrepreneurial intentions. Research limitations/implications: The study has a few limitations because, as it refers to the sample for college students and the new start-up, it would require a more generalized analysis of the factors, such as to include more and better indicators for demographic, economic and institutional determinants of the entrepreneurial intentions and entrepreneurship. For further studies on entrepreneurship, the validate measuring scale of the concept must be addressed. Practical implications: The present work shows that optimizing the entrepreneurial environment and improving the entrepreneurial ability of college students can enhance the success rate of the entrepreneurship. Besides, the entrepreneurial intentions should be enhanced from outside to inside. Namely, stimulate the entrepreneurial desire of college students from the external environment, such as policy support, ideological education and mobilization on employment options and other aspects of new college graduates. The psychological aspects of graduates should be guided. Originality/value: For the study of entrepreneurial intentions, most scholars mainly studied the entrepreneurial psychology to discuss its relationship with entrepreneurial intentions in the early years, and gradually extended to the study of external factors, such as the entrepreneurial environment. However, the study on graduate entrepreneurship has yet to be improved. Based on the existing research, this paper makes an in-depth study on the influence mechanism of entrepreneurial intentions from entrepreneurial ability and entrepreneurial environment, puts forward a research model taking self-actualization as a mediating variable and studies the intrinsic driving force of entrepreneurial intentions.